Perlindungan Petani Atas Pendistribusian Bibit Tanaman di Padang Lawas Utara Perspektif Maslahah Mursalah - Dakkal Sentosa Harahap; Rahmad Efendi (LPPM Universitas Ekasakti Padang, 2023)
Forms of policy that can be provided to protect Farmers' interests include regulating imports of Agricultural Commodities in accordance with the harvest season and/or domestic consumption needs; providing agricultural production facilities that are timely, of the right quality and at affordable prices for farmers, as well as subsidies for production facilities. The aim of this research is to determine legal protection for farmers who receive distribution of rice seeds in the District. North Padang Lawas, obstacles and efforts. Data analysis in this research uses qualitative analysis with primary data sources obtained from the District Agriculture Service. North Padang Lawas and from the Farmers Group. Based on the research results, the legal concept of protection for farmers is the protection of farmers' rights. In terms of regulations, legal protection for farmers is regulated in Law Number 41 of 2009 concerning Protection of Food Agricultural Land which has been replaced by Law and Law Number 19 of 2013 concerning Protection and Empowerment of Farmers; Legal protection for farmers who receive rice seed distribution facilities in the District. Padang Lawas Utara by facilitating farmers to obtain distribution of rice seeds, such as providing information to farmers about the mechanism for obtaining plant seeds to be distributed. In implementing legal protection for farmers in Kab. In North Padang Lawas there are obstacles, namely regarding the distribution of plant seeds that do not comply with the provisions set by the government and the lack of communication interaction between the district Agriculture Service. North Padang Lawas with farmer groups. Efforts made are to systematically collect data on farmer groups and improve communication with farmer groups.